Examining unidimensionality and improving reliability for the eight subscales of the SF-36 in opioid-dependent patients using Rasch analysis. - Hsiao, Yu-Yu; Shih, Ching-Lin; Yu, Wan-Hui; Hsieh, Cheng-Hsi; Hsieh, Ching-Lin (Quality of Life Research, 2015)
Purpose: The Medical Outcome Study Short Form 36 (SF-36) is one of the most commonly used questionnaires for monitoring the Health-Related Quality of Life (HRQOL) of opioid-dependent patients. However, the unidimensionality and reliability of the SF-36 have not been verified in opioid-dependent patients. The aim of this study was to examine the unidimensionality and to improve the test reliability of the SF-36 for use in opioid-dependent patients.Methods: A total of 583 opioid-dependent patients were recruited in the study. Unidimensionality was examined by conducting unidimensional Rasch analysis. Item fit statistics and principle component analysis were used to check the item-model fit in each of the eight subscales of the SF-36. Reliability was evaluated by applying both unidimensional and multidimensional Rasch analyses.Results: After three misfitting items were excluded, the remaining items of each subscale in the SF-36 represented a single construct. The test reliabilities (0.80-0.87) yielded by the multidimensional approach were much higher than those (0.68-0.82) produced by the unidimensional approach.Conclusion: The remaining 32 items of the SF-36 are appropriate for evaluating the HRQOL in opioid-dependent patients in terms of unidimensionality. Additionally, the test scores produced by the multidimensional approach were more accurate than those obtained by the unidimensional approach.